An Evaluation of Antibiotic Prescribing Practices Upon Hospital Discharge. (28th November 2016) - Scarpato, Sarah J.; Timko, Daniel R.; Cluzet, Valerie C.; Dougherty, Jillian P.; Nunez, Jonathan J.; Fishman, Neil O.; Hamilton, Keith W.
Abstract : We conducted a retrospective study of the appropriateness of antimicrobial agents prescribed on discharge from an acute care hospital. Seventy percent of discharge antibiotics were inappropriate in antibiotic drug choice, dose, or duration. Our findings suggest there is a significant need for antimicrobial stewardship at transitions in care. Infect Control Hosp Epidemiol 2017;38:353–355